Diversity and distribution of corals with emphasis on morphological structures and phylogenetic analyses of Euphyllidae corals in Tioman, Redang and Payar Islands, Malaysia - Mohd Fikri Akmal bin Khodzori (Kulliyah of Science, International Islamic University Malaysia, 2016)
Understanding on the current status of coral diversity and distribution in Peninsular Malaysia are important for sustainable coral reef ecosystem management. The present study aims to determine the diversity and distribution of corals using the Coral Video Transect (CVT) method at 35 sampling stations in the coast of Tioman, Redang and Payar Islands. Coral Point Count with Excel extention (CPCe) software was used to analyse the images for the identification and coral coverage measurement. The findings of this study showed that the corals around Tioman and Redang Islands were in a ‗good' condition with the average coverage of live corals were 51.4% ± 1.6 and 50.8% ± 2.6, respectively. Whereas, the corals around Payar Island were in a ‗poor' condition with the average coverage of live corals was 14.8% ± 6.1. Tioman Island had the highest number of coral genera and families (65 genera, 21 families) compared to Redang (55 genera, 17 families) and Payar Islands (39 genera, 14 families). Tioman Island also showed the highest average diversity index of coral genera (H' = 2.57 ± 0.1), followed by Redang (H' = 2.40 ± 0.1) and Payar Islands (H' = 1.92 ± 0.1). Rapid, intensive and unsustainable coastal developments, increasing number of tourists and shortcomings in environmental conservations are believed to be the factors which influenced the coral condition and genera richness in these islands. Based on the multivariate analysis, genera Acropora, Montipora and Porites were dominated in Tioman, Acropora, Fungia and Pocillopora in Redang and Porites and Physogyra in Payar Islands. These coral genera are able to tolerate with wide changes in environmental conditions, such as currents, wave actions and high suspended sediment concentrations. One sample t-test showed that the dominant corals differed significantly among sampling stations. Mixed coral morphological structures of branching corals (Acropora and Pocillopora), encrusting and foliose coral (Montipora), mushroom coral (Fungia), massive corals (Porites, Favia, Favites, Platygyra) and sub-massive coral (Galaxea) were dominant in Tioman and Redang Islands. However, stress tolerator corals such as massive coral (Porites) and massive-platy coral (Physogyra) were dominant in Payar Island. The morphological structures and phylogenetic analyses based on the mitochondrial cytochrome oxidase subunit 1 (CO1) gene have identified a total of six Euphyllidae coral species in this study. Euphyllia ancora had the highest average percentage coverage and dominant in Tioman, Plerogyra sinuosa in Redang and Physogyra lichtensteini in Payar Islands. The diversity and distribution of these endangered Euphyllidae coral species are believed to be influenced by the difference in reef morphology, type of substrates and environmental conditions. As conclusion, this study has provided important information on the current status of corals including the rare and endangered Euphyllidae species for comprehensive marine conservation and effective management plan to sustainably manage coral reef ecosystems in marine protected areas of Peninsular Malaysia.